Delay in Clozapine Initiation in Patients with Treatment-Resistance Schizophrenia Presenting Tertiary Psychiatric Facilities - Jan, Asad Ullah; Rahim, Sajid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the delay in Clozapine initiation in patients with treatment-resistance schizophrenia who presented to the Tertiary psychiatric facilities. Study Design: Cross-sectional study. Place and Duration of Study: Department of Psychiatry Combined Military Hospital, Peshawar and Department of Psychiatry Combined Military Hospital, Nowshera Pakistan, from Jan to Dec 2023. Methodology: We recruited 103 treatment-resistant schizophrenia and Clozapine naïve patients after obtaining their consent. Patients were included by reviewing their medical history and records. The diagnosis was made by clinical interview and use of Positive and Negative syndrome scale. The data were recorded using a semi-structured questionnaire. Results: Out of 103 patients, 78(75.7%) were male and 25(24.3%) were female. Regarding the initiation of Clozapine treatment, the mean duration from diagnosis to treatment initiation was 6.23±4.82 years. Patients were categorised based on the time to Clozapine initiation into early initiators (≤4 years), intermediate initiators (>4 years to <15 years), and delayed initiators (>15 years). The distribution across these categories was 51(49.5%) for early initiators, 47(45.6%) for intermediate initiators, and 5(4.9%) for delayed initiators. Conclusion: There is a significant delay in Clozapine initiation despite adequate evidence to initiate it early. Clinicians should start Clozapine whenever there is a need.